Factors Affecting the Adoption of Advanced IT with Specific Emphasis on Building Information Modeling Based on TOE Framework: A Systematic Review - Elghdban, Mohamed Ghayth; Nurhidayah, Azmy; Adnan, Zulkiple; Al-Sharafi, Mohammed A. (Science & Engineering Research Support Society, 2020)
Despite the sensitivity of the architecture, engineering, and construction (AEC) industry to changes in demographic factors, economic activity, & social development, the industry is consistently progressing and becoming more successful. However, organizations in the AEC industry are lagging in the adoption of advanced IT; for instance, Building Information Modelling (BIM) is one of the top technologies used in the industry. BIM is extensively known as one of the innovations of IT to have emerged within the AEC industry. Although BIM processes require organization-wide adoption, few studies have focused on the technological, organizational, and environmental (TOE) factors influencing BIM adoption at the organizational level in the AEC industry. Therefore, this study aims to further enrich the literature of such studies through a systematic literature review (SLR). This SLR primarily aims to analyze the existing studies that involved the TOE factors that influence organizations to adopt and use advanced IT, such as BIM. Therein, 104 up-to-date studies retrieved from two primary databases (Scopus and Web of Science) were critically analyzed in the period between 2015 and October 2019. The review identified 42 factors related to the technological context, 71 factors related to the organizational context, and 59 factors related to the environmental context which are believed to influence the adoption and use of BIM in the AEC industry. The outcome of this SLR will add significantly to the existing literature in IT adoption in general, and BIM adoption practically.